U C Berkeley Co-op Friends 18th Annual Heavy-St. Francis Hotel - Watkins, Howard::::::::: (1986)
Floor: Cynthia Nicholson, Greg Nicholson, Howard Watkins and Christine Watkins; seated: David Atkinson, Teresa Pricco, Terri Mesple, David Morse and Bonnie Neary; standing: Kathy Muniz, Denise Morse, Jerry Neary, Alan Pricco and Dale Mesple Photo taken with timer on camera